Master signifiers, ideological fantasy, unknowability, and enjoyment in the colonial field - Hook, Derek (PINS-Psychology in Society, 2018)
Chabani Manganyi’s long-neglected (2018) essay “Making strange” demonstrates how many of the most influential philosophical and psychological discourses of Western modernity are fundamentally extensions of colonial discourse, a fact evinced in a reoccurring discursive device: the production of otherness. This paper argues that the procedures through which otherness is produced are not only discursive but psychical also. They are discursive in the sense that discourses of racial knowing perpetuate – by their own constant failure to fully know – the need to try yet again to know the unknowable, that is, to produce unknowability. They are psychical in the sense of a fundamental fantasmatic assumption of a counter-identification, that is, via an already made assumption of fundamental difference. So, while the argument is sometimes made – as it is, in exemplary fashion in Manganyi’s work – that psychoanalysis cannot rid itself of the conceptual shadow of colonial discourse, it can also be said that the critiques of colonial discourse are themselves are often tied to, if not implicitly contingent upon, extensions and adaptations of psychoanalytic ideas.